Protecting personal medical information: Asian perspectives - Samsuri, Suhaila; Ismail, Zuraini; Ahmad, Rabiah (International Association of Computer Science and Information Technology Press, 2013)
In order to tackle the issue of privacy concern over the personal information management system, this paper begins with the gathering of views on information privacy and how culture has influenced among several Asian countries including India, Thailand, Japan, China and Malaysia. In accordance to the culture dimension theory of Hofstede, it attempts to reveal the perception and concern of several Asian countries towards the privacy of their personal medical information. The previous studies found that Asian communities have a distinctive concept in perceiving the value of information privacy, which is completely unique from the description set by western countries. The findings are considered as valuable and usable in designing the patient’s electronic medical record (EMR) system in hospital information system (HIS) with the incorporation of privacy preservation elements.